Introduction to sociology / Anthony Giddens ...[et al] - Appelbaum, Richard P.
Introduction to Sociology focuses only on what students need to know in order to master the sociological concepts taught in the introductory course. Each chapter in the Tenth Edition follows the same consistent four-part structure: First, the authors introduce the basic concepts before discussing sociological theory. They then turn their attention to current research and finally wrap up by exploring unanswered questions that face sociologists today. This consistent, thoughtful organization―coupled with Learning Objectives, Concept Checks, and Big Picture concept maps―keeps students focused on the core concepts. Now supported by InQuizitive, the Tenth Edition builds on the book’s long-standing strengths: emphasis on linking micro and macro sociology, coverage of the best recent research, and an exceptionally affordable price relative to other comprehensive texts